Recent advances in the development and application of colorectal cancer mouse models - Wang, Ting; Chen, Zhen; Zhang, Yuli; Liu, Min; Sui, Hua; Tang, Qingfeng (Frontiers in Pharmacology, 2025)
Colorectal cancer (CRC) remains a significant global health challenge, necessitating the development of reliable preclinical models to advance mechanistic understanding and therapeutic innovation. This review comprehensively examines the diverse spectrum of rodent models employed in CRC research, focusing on their unique characteristics, applications, and translational relevance. We systematically evaluate conventional models, including carcinogen-induced models and genetically engineered mouse models (GEMMs), which have been instrumental in elucidating tumorigenic pathways and genetic drivers. Furthermore, we highlight the emergence of patient-derived xenografts (PDX) as a transformative tool for recapitulating tumor heterogeneity and predicting clinical responses. The review also explores metastatic models, which are critical for studying advanced disease, and spontaneous models that mimic natural tumor progression. Additionally, we discuss the growing utility of composite animal models, which integrate multiple methodologies to better reflect the complexity of human CRC. By comparing the strengths and limitations of each model system, this review provides a framework for selecting appropriate models based on specific research objectives. Collectively, these preclinical platforms have significantly advanced our understanding of CRC biology and continue to drive the development of targeted therapies and personalized treatment strategies.